GROWTH PERFORMANCE AND HAEMATOLOGICAL AND HORMONAL PROFILE OF JAFFRABADI BUFFALO HEIFERS SUPPLEMENTED WITH RUMEN BYPASS LYSINE AND METHIONINE - Odedra, MD; Ravikala, K; Killedar, A; Sarvaiya, NP; Padodra, RJ (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
An experiment was conducted to evaluate supplementation of rumen protected LYS (lysine) and MET (methionine) on haematological and hormonal profile in Jaffrabadi buffalo heifers. Eighteen buffalo heifers aged 15-21 months of University farm were randomly divided into three groups each of 6 animals and receiving one of the three dietary treatments for a period of 180 days, viz., T1- DCP requirement met through concentrate mixture, T2-DCP requirement through cottonseed cake and concentrate mixture (50:50) and T3- DCP requirement through concentrate mixture with supplementation of rumen bypass LYS and MET @ 5.0 g and 2.5 g/day/animal, respectively. Changes in the body weight, haematology and plasma profile of gonadal steroid hormones were estimated on day 0, 90 and 180 of treatment periods. Weight gain of heifers was significantly improved with T3; however there was no effect of dietary treatments or periods on the hematological values or plasma estradiol and progesterone profile of experimental heifers. Mean values for the entire periods for estradiol and progesterone were 22.61±4.18, 22.28±3.59, 31.00±9.03 pg/ml and 0.24±0.05, 0.15±0.03, 0.20±0.06 ng/ml, respectively. A linear response with regard to estradiol level was observed only in T3 group. It was inferred that inclusion of bypass LYS and MET @ 5.0 g and 2.5 g per day/animal in diet, though significantly enhanced body weight gain, has no significant effect on haematological and hormonal parameters in Jaffrabadi buffalo heifers.
Keywords: Lysine; Methionine; Jaffrabadi heifers; Estradiol